Pelayanan Berbasis Online Pada Aplikasi Sistem Informasi Manajemen Pelayanan (SIMPEL) Di Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Provinsi Riau - Aidillia Akhwany; Rijalul Fikri (Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
Online-Based Services on the Service Management Information System (SIMPEL) Application at the Riau Province Investment and One-Stop Integrated Services Office experienced problems, namely openness in the follow-up process where the public often does not receive clear information, indicating a lack of coordination. between field units, there are indications of technical problems with online services. The purpose of this study is to find out online-based services on the service management information system application (SIMPEL) at the Riau Province Investment and One-Stop Integrated Services Office. The research method used was a qualitative descriptive research. The data collection techniques use library research and field studies consisting of observation, interviews and documentation. The data analysis techniques used are data reduction, data display and verification. Based on the research results, it was concluded that the implementation of online-based licensing services in general has not run optimally considering that the online-based licensing service program is an innovation program that has just been implemented at DPMPTSP.  Efforts made to face obstacles include optimizing systems and information, effective communication, ongoing evaluation, close collaboration with the IT Team and periodic evaluation and adjustments. Maximize service delivery both in terms of process and service output and the Department must be able to accommodate complaints from each applicant and improve service performance at the Riau Province One-Stop Integrated Services and Investment Service.